Primary and adjuvant intensity-modulated radiotherapy in oropharyngeal carcinoma patients from a single institution - Hauswald, Henrik; Petrow, Eugen; Röder, Falk; Debus, Jürgen; Zwicker, Felix; Huber, Peter E. (Journal of cancer research and therapeutics, 2024)
Background: To retrospectively access outcome, adverse events and prognostic factors in oropharyngeal carcinoma (OPC) patients treated with intensity-modulated radiotherapy (IMRT). - Methods: Ninety-eight OPC patients were treated between 2000 and 2015. Thirty-three patients received definitive and 65 adjuvant radiotherapy. Seventy-one percent had simultaneous chemotherapy. Patients were systematically followed up (mean 114 months, range 19-197 months). Statistical analysis used Kaplan-Meier method, Cox regression analysis, and log-rank test. Adverse events were classified according to common toxicity criteria version (CTCAE) 4.03. - Results: The 1-, 5-, and 10-year overall survival rates in the adjuvant vs. definitive cohort were 90.8% vs. 66.7%, 67.4% vs. 33.1%, and 57.7% vs. 16.5%. Survival in the adjuvant cohort was significantly longer than in the definitive cohort (P < 0.00005). Patients <65 years had a significantly longer survival than older patients. Locoregional tumor control rates after 1-, 5-, and 10 years in the adjuvant vs. definitive cohort were 90.2% vs. 66.7%, 82.2% vs 45.4%, and 72.1% vs. 30.3%. Locoregional tumor control in the adjuvant cohort was significantly longer than in the definite cohort (P < 0.005). Distant metastases were diagnosed in 20.4% of all patients. Most patients had mild CTCAE grade 1 and 2 adverse events and mild late adverse events including xerostomia, dysphagia, and lymphedema. - Conclusion: Intensity-modulated radiotherapy for OPC is an important part of the treatment algorithm alone and in particular after surgery while the additional benefits of chemotherapy might be age dependent. Despite advanced tumor stages, nearly half of our patients were alive in the long term. The majority of patients had relatively mild chronic adverse events.
Verfügbar: 04‑Apr‑2023
Gesehen am 11.11.2024